Dissuading Terror Strategic Influence and the Struggle Against Terrorism - Cragin, Kim (RAND Corporation, 2005)
U.S. government decisionmakers face a number of challenges as they attempt to form policies that aim to dissuade terrorists from attacking the United States, divert youths from joining terrorist groups, and persuade the leaders of states and nongovernmental institutions to withhold support for terrorists. The successes or failures of such policies and campaigns have long-lasting effects. The findings of this research help U.S. decisionmakers more closely refine how and in what circumstances strategic influence campaigns can best be applied.